A cluster‐randomized controlled trial of a combination HIV risk reduction and microfinance intervention for female sex workers who use drugs in Kazakhstan. Issue 5 (5th May 2021) - El‐Bassel, Nabila; McCrimmon, Tara; Mergenova, Gaukhar; Chang, Mingway; Terlikbayeva, Assel; Primbetova, Sholpan; Kuskulov, Azamat; Baiserkin, Bauyrzhan; Denebayeva, Alfiya; Kurmetova, Kulpan; Witte, Susan S.
Abstract: Introduction: Female sex workers (FSW) who use drugs are a key population at risk of HIV in Kazakhstan, and face multiple structural barriers to HIV prevention. More research is needed on the role of structural interventions such as microfinance (MF) in reducing HIV risk. This paper describes the results of a cluster‐randomized controlled trial to test the efficacy of a combination HIVRR + MF intervention in reducing biologically confirmed STIs and HIV risk behaviours. Methods: This study took place from May 2015 to October 2018 in two cities in Kazakhstan. We screened 763 participants for eligibility and enrolled 354 FSW who use drugs. Participants were randomized in cohorts to receive either a four‐session HIVRR intervention, or that same intervention plus 30 additional sessions of financial literacy training, vocational training and asset‐building through a matched‐savings programme. Repeated behavioural and biological assessments were conducted at baseline, 3‐, 6‐ and 12‐months post‐intervention. Biological and behavioural primary outcomes included HIV/STI incidence, sexual risk behaviours and drug use risk behaviours, evaluated over the 12‐month period. Results: Over the 12‐month follow‐up period, few differences in study outcomes were noted between arms. There was only one newly‐detected HIV case, and study arms did not significantly differ on any STI incidence. At post‐intervention assessments compared to baseline, both HIVRR and HIVRR + MF participants significantly reduced sexual and drug use risk behaviours, and showed improvements in financial outcomes, condom use attitudes and self‐efficacy, social support, and access to medical care. In addition, HIVRR + MF participants showed a 72% greater reduction in the number of unprotected sex acts with paying partners at the six‐month assessment (IRR = IRR = 0.28, 95% CI = 0.08, 0.92), and a 10% greater reduction in the proportion of income from sex work at the three‐month assessment (b = −0.10, 95% CI = −0.17, −0.02) than HIVRR participants did. HIVRR + MF participants also showed significantly improved performance on financial self‐efficacy compared to HIVRR over the 12‐month follow‐up period. Conclusions: Compared to a combination HIVRR + MF intervention, a robust HIVRR intervention alone may be sufficient to reduce sexual and drug risk behaviours among FSW who use drugs. There may be structural limitations to the promise of microfinance for HIV risk reduction among this population.